Intrinsic polarization coupling in 2D α‐In2Se3 toward artificial synapse with multimode operations. (8th February 2021) - Gao, Jing; Zheng, Yue; Yu, Wei; Wang, Yanan; Jin, Tengyu; Pan, Xuan; Loh, Kian Ping; Chen, Wei
Abstract: Emulation of advanced synaptic functions of the human brain with electronic devices contributes an important step toward constructing high‐efficiency neuromorphic systems. Ferroelectric materials are promising candidates as synaptic weight elements in neural network hardware due to their controllable polarization states. However, the increased depolarization field at the nanoscale and the complex fabrication process of the traditional ferroelectric materials hamper the development of high‐density, low‐power, and highly sensitive synaptic devices. Here, we report the implementation of two‐dimensional (2D) ferroelectric α‐In2 Se3 as an active channel material to emulate typical synaptic functions. The α‐In2 Se3 ‐based synaptic device features multimode operations, enabled by the coupled ferroelectric polarization under various voltage pulses applied at both drain and gate terminals. Moreover, the energy consumption can be reduced to 1 pJ by using high‐ κ dielectric (Al2 O3 ). The successful control of ferroelectric polarizations in α‐In2 Se3 and its application in artificial synapses are expected to inspire the implementation of 2D ferroelectric materials for future neuromorphic systems. Abstract : In this paper, an artificial synapse with multi‐mode operations is developed based on 2D semiconductor α‐In2 Se3 with intrinsically coupled in‐plane and out‐of‐plane ferroelectric polarization. Various synaptic functions have been emulated by the device. Advantages like simple structure, multi‐mode operations, rich functions as well as low‐energy consumption make 2D ferroelectric materials promising for future neuromorphic applications.